Cerebrovascular Risk Profiles in a Saudi Arabian Cohort of Young Stroke Patients - Eltemamy, Marwa Ahmed; Tamayo, Arturo; Altarsha, Eyad; Sedghi, Annahita; Pallesen, Lars-Peder; Barlinn, Jessica; Puetz, Volker; Illigens, Ben Min-Woo; Barlinn, Kristian; Siepmann, Timo (Frontiers in Neurology, 2021)
Background: The constantly increasing incidence of stroke in younger individuals substantiates an urgent need for research to elucidate underlying risk factors and etiologies. Heretofore, the vast majority of studies on stroke in the young have been carried out in European and North American regions. We aimed to characterize cerebrovascular risk profiles in a Saudi Arabic cohort of consecutive young stroke patients. Methods: We retrospectively analyzed data from consecutive ischemic stroke patients aged 15 to 49 years who underwent detailed cardiocerebrovascular evaluation at a tertiary stroke care center in Makkah, Saudi Arabia. Distributions of risk factors and stroke etiologies were assessed in the entire cohort and in two strata of very young (15–40 years) and young to middle-aged patients (41–49) to account for variability in suggested age cutoffs. Results: In the entire cohort [n = 63, ages 44 (34–47) median, interquartile range], dyslipidemia (71.4%) and small vessel occlusion (31.7%) displayed highest prevalence followed by diabetes (52.4%) and cardioembolism (19%). In very young patients, cardioembolism was the most prevalent etiology (27.3%). Risk profiles were similar between both age strata except for a higher prevalence of diabetes among the older cohort (31.8 vs. 63.4%, p = 0.01). Logistic regression identified diabetes as strongest predictor for association to the older strata (odds ratio = 4.2, 95% confidence interval = 1.2–14.1, p = 0.02). Conclusion: Cerebrovascular risk profiles and stroke etiologies in our cohort of young stroke patients differ from those of previous cohorts, suggesting the need for tailored prevention strategies that take into account local epidemiological data on cerebrovascular health.